PENDAMPINGAN PROGRAM KAMPUS MENGAJAR SEBAGAI FLAGSHIP MBKM DI SDN 1 KUALA PEMBUANG 1 - Tirsa Neyatri Bandrang (Jurnal Pengabdian Kepada Masyarakat Agri Hatantiring, 2024)
The Teaching Campus Program is one of the flagships in the Independent Learning Independent Campus (MBKM) policy which aims to improve the quality of basic education in Indonesia, especially in the aspects of literacy, numeracy, and student character. This program involves students as agents of change in helping elementary schools face various educational challenges, such as low literacy and numeracy levels, as well as limited teaching staff. In order to support the success of the program, this community service activity is carried out with a focus on assisting the Teaching Campus Program at SDN 1 Kuala Pembuang 1. This assistance aims to provide guidance and training to students participating in the Teaching Campus, teachers, and the school so that the program can run optimally and sustainably. The methods used in this activity include initial observation, training, direct mentoring, and program evaluation. Initial observations are made to identify school conditions, challenges faced, and specific needs needed by teachers and students. After that, training was carried out for students participating in the Teaching Campus related to innovative teaching techniques, the use of digital learning media, and effective strategies to increase literacy and numeracy. In addition, assistance is also provided to teachers and schools in utilizing available resources and integrating Teaching Campus activities with the school curriculum. The results of this mentoring activity show an increase in student understanding in implementing more interactive and technology-based teaching strategies. Teachers at SDN 1 Kuala Pembuang 1 also benefited from this activity, especially in terms of increasing teaching capacity and using technology in learning. In addition, students involved in this program experienced an increase in learning motivation, especially in the aspects of literacy and numeracy. Other indicators of success can be seen from the school's positive response to the sustainability of this program and the proposal to implement a similar mentoring model in the following years. Although this activity has a positive impact, there are several challenges faced, such as limited technological infrastructure in schools, limited time for students to run programs, and coordination between students, teachers, and the school. Therefore, the recommendations given include the need to strengthen synergy between universities, schools, and local governments in supporting the Teaching Campus program in a sustainable manner. In addition, it is necessary to develop a more flexible training model and provide adequate technological resources so that the implementation of the program is more effective. Overall, the mentoring activities of the Teaching Campus Program at SDN 1 Kuala Pembuang 1 show that this program has great potential in improving the quality of education in elementary schools, especially in the aspects of literacy, numeracy, and student character. With systematic and need-based assistance, the Teaching Campus Program can be one of the effective solutions in supporting the improvement of the quality of basic education in Indonesia. It is hoped that this activity can continue to be developed and applied in various other schools to achieve better national education goals.